2016
DOI: 10.18632/oncotarget.12796
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma levels of HIF-1a and PGC-1a in breast cancer

Abstract: Cellular adaptive mechanisms are crucial for tumorigenesis and a common feature in solid tumor progression. Hypoxia-inducible factor-1α (HIF-1α) facilitates the biological response to hypoxia, advancing angiogenesis and metastatic potential of the tumor. The peroxisome proliferator–activated receptor γ coactivators 1α (PGC-1α) enhances mitochondrial biogenesis, favored by migratory/invasive cancer cells. We conducted a prospective, long-term follow up study to determine whether HIF-1α and PGC-1α can be impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…An increased reliance on OXPHOS with a marked shift away from aerobic glycolysis was observed in glioma stem cells [ 40 ]. Similarly, high PGC1α and HIF1α levels have been suggested as effective and non-invasive plasma biomarkers of poor prognosis for patient with breast cancer [ 41 ]. The findings of the present study support a role for PGC1α in the regulation of oncogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…An increased reliance on OXPHOS with a marked shift away from aerobic glycolysis was observed in glioma stem cells [ 40 ]. Similarly, high PGC1α and HIF1α levels have been suggested as effective and non-invasive plasma biomarkers of poor prognosis for patient with breast cancer [ 41 ]. The findings of the present study support a role for PGC1α in the regulation of oncogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that HIF1-α overexpression was detected in a variety of solid tumors (20). Meanwhile, recent studies have shown that in oral squamous cell carcinoma (21), esophageal squamous cell carcinoma (22), renal clear cell carcinoma (23) and breast cancer (24), HIF1-α expression was correlated with cancer metastasis. In our study, we demonstrated that 57 cases of 103 samples were HIF1-α-positive, and consistent with previous findings (25), HIF1-α levels were associated with BMPR2, bone morphogenetic protein receptor 2; HIF1-α, hypoxia-inducible factor 1-α; ROC, receiver operating characteristics; 95% CI, 95% confident interval; +, positive; -, negative; † , included BMPR2+HIF1-α-, BMPR2-HIF1-α+, and BMPR2-HIF1-α-.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients exhibit significantly high HIF-1α levels, which correlate with more aggressive cancer features, and particularly with a poor disease free and overall survival 52 . Our results showed that HT (50-200 µM) decreased HIF-1α protein level without modulating its mRNA expression.…”
Section: Discussionmentioning
confidence: 99%